Aplicaciones en la biometalurgia - Ho Lock, Delia (2009)
Biometallurgical applicationsThe present work had two parts: First, it was the bioleaching of three sulfide minerals using Acidithiobacillus microorganism as a bioleaching agent. The main goal is to show the leaching capacity of the bacteria and its commercial application. In the second part, a refractory gold sulfide ore was used to study the release of gold from its matrix